The Lateral Line System - Coombs, Sheryl; Bleckmann, Horst; Fay, Richard R.; Popper, Arthur N.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
The Lateral Line System provides an overview of the key concepts and issues surrounding the development, evolution, neurobiology, and function of the lateral line, a fascinating yet somewhat enigmatic flow-sensing system. The book examines the historical precedence for linking the auditory and lateral line systems, its structure and development, use of the lateral line system of zebrafish as a model system, physical principles governing the response properties of the lateral line, the behavioral relevance of this sensory system to the lives of fish, and an examination of how this information is shaped and encoded by the peripheral and central nervous systems. Contents The Gems of the Past: A Brief History of Lateral Line Research in the Context of the Hearing Sciences - Sheryl Coombs and Horst Bleckmann Morphological Diversity, Development, and Evolution of the Mechanosensory Lateral Line System - Jacqueline F. Webb The Hydrodynamic of Flow Stimuli - Matthew J. McHenry and James C. Liao The Biophysics of the Fish Lateral Line - Sietse M. van Netten and Matthew J. McHenry Sensory Ecology and Neuroethology of the Lateral Line - John Montgomery, Horst Bleckmann, and Sheryl Coombs Information Encoding and Processing by the Peripheral Lateral Line System - Boris Philippe Chagnaud and Sheryl Coombs The Central Nervous Organization of the Lateral Line System - Mario F. Wullimann and Benedikt Grothe Central Processing of Lateral Line Information - Horst Bleckmann and Joachim Mogdans Functional Overlap and Nonoverlap Between Lateral Line and Auditory Systems - Christopher B. Braun and Olav Sand The Hearing Loss, Protection, and Regeneration in the Larval Zebrafish Lateral Line - Allison B. Coffin, Heather Brignull, David W. Raible, and Edwin W Rubel About the Editors: Sheryl Coombs is Professor of Biological Science at Bowling Green State University. Horst Bleckmann is Professor in the Institute for Zoology at the University of Bonn. Arthur N. Popper is Professor in the Department of Biology and Co-Director of the Center for Comparative and Evolutionary Biology of Hearing at the University of Maryland, College Park. Richard R. Fay is Distinguished Research Professor of Psychology at Loyola University Chicago. About the series: The Springer Handbook of Auditory Research presents a series of synthetic reviews of fundamental topics dealing with auditory systems. Each volume is independent and authoritative; taken as a set, this series is the definitive resource in the field.
The Gems of the Past: A Brief History of Lateral Line Research in the Context of the Hearing Sciences -- Morphological Diversity, Development, and Evolution of the Mechanosensory Lateral Line System -- The Hydrodynamic of Flow Stimuli -- The Biophysics of the Fish Lateral Line -- Sensory Ecology and Neuroethology of the Lateral Line -- Information Encoding and Processing by the Peripheral Lateral Line System -- The Central Nervous Organization of the Lateral Line System -- Central Processing of Lateral Line Information -- Functional Overlap and Nonoverlap Between Lateral Line and Auditory Systems -- The Hearing Loss, Protection, and Regeneration in the Larval Zebrafish Lateral Line.
Keywords: Medicine; Neurosciences; Neurology; Biomedicine; Neurosciences; Neurology